Globalisasi dan Hak Asasi Manusia: Tinjauan Kritis Terhadap Wacana Global Governance dalam Upaya Perlindungan Pekerja Migran Indonesia - Permana, Rengga Dina (Jurnal Keamanan Nasional, 2018)
The discourse of Global Governance came along with globalization. This article will not show the reader the debates among scholars regarding the wide definition of globalization, rather this article is a production of critical consciousness. Using Foucault’s governmentality in order to dismantle the technology of power this article explains how then globalization with the issues that came along with its discourse. In this case, I raise the human rights issue that becoming the political rationalization of protecting migrant workers must be started from human rights discourse and take it as the regime of truth.